0613 The Effects of Diabetes on Obstructive Sleep Apnea Severity and Progression: A Propensity Score Analysis. (27th May 2020) - Li, Q; Keenan, B T; Punjabi, N M; Maislin, G; Kuna, S T
Abstract: Introduction: Obstructive sleep apnea (OSA) is associated with increased glucose intolerance and insulin resistance, and commonly coexists with type 2 diabetes mellitus (T2DM). Research suggests an independent association between these two conditions. However, more research into the role of T2DM in the development of OSA, or vice versa, is needed. Methods: Leveraging data from 139 participants with T2DM from the Sleep AHEAD cohort and 5, 085 participants without T2DM from the Sleep Heart Health Study (SHHS), we conducted two complementary propensity score (PS) subclassification analyses to estimate the effect of T2DM on the oxygen desaturation index (ODI), both at baseline and over 4-5 years of follow-up. PS models included age, sex, race, body mass index, neck circumference, waist circumference, total cholesterol, HDL cholesterol, triglycerides, Epworth Sleepiness Scale, and comorbid hypertension or cardiovascular disease. Models evaluating ODI progression also included baseline ODI. Results: The PS subclassification analysis identified 109 participants with T2DM and 480 without T2DM, balanced with respect to baseline covariates, for evaluation of the effect of T2DM on baseline ODI. On average, those with T2DM had a 9 events/hour greater ODI compared to those without (24.3 [20.8, 27.9] vs. 15.3 [13.6, 16.9] events/hour; p<0.0001). Among patients with baseline ODI≥5, a second PS subclassification identified 99 with T2DM and 227 without for evaluating the effect of T2DM on ODI progression. No difference in change in ODI was observed between those with and without T2DM (mean [95% CI] difference -0.25 [-10.7, 10.2] events/hour; p=0.963). Conclusion: Using two robust PS subclassification designs to minimize selection bias, we evaluated the effect of T2DM on baseline ODI and ODI progression in adults with OSA after 4-5 years. Those with T2DM had more severe baseline ODI, but there were no meaningful differences in ODI progression. Results further our understanding of the association between these coexisting conditions. Support: NIH grant HL070301